2020
DOI: 10.1007/s00423-019-01850-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender comparison of clinical, histopathological, therapeutic and outcome factors in 185,967 colon cancer patients

Abstract: Introduction Colorectal carcinomas represent the third most common cause of cancer-related deaths in Germany. Although the incidence is significantly higher in men compared with women and gender is a well-established crucial factor for outcome in other diseases, detailed gender comparisons for colon cancer are lacking. Methods This retrospective population-based cohort study included all patients diagnosed with colon cancer in Germany between 2000 and 2016 who were included in the common dataset of colorectal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 26 publications
2
49
0
1
Order By: Relevance
“…In addition, men who are diagnosed with colorectal cancer have a worse prognosis and approximately 40% higher mortality compared to women [ 17 ]. On the other hand, women are more prone to develop right-sided colon cancer, which is often diagnosed at a more advanced stage and seemed more aggressive than left-sided tumors [ 64 , 65 ]. The reasons for sex disparity are not fully understood, it is considered that they may be related to the differences in the exposure to risk factors (e.g., alcohol and tobacco), dietary patterns and sex hormones [ 17 , 47 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…In addition, men who are diagnosed with colorectal cancer have a worse prognosis and approximately 40% higher mortality compared to women [ 17 ]. On the other hand, women are more prone to develop right-sided colon cancer, which is often diagnosed at a more advanced stage and seemed more aggressive than left-sided tumors [ 64 , 65 ]. The reasons for sex disparity are not fully understood, it is considered that they may be related to the differences in the exposure to risk factors (e.g., alcohol and tobacco), dietary patterns and sex hormones [ 17 , 47 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several retrospective studies have shown female CRC patients to have longer survival rates than male patients. For example, a German population-based cohort study including 185,967 patients showed women had significantly better overall (HR 0.853) and recurrence-free survival (HR 0.857) than men ( 10 ). A meta-analysis from 2017 including 37 clinical trials determined that women had better overall (HR 0.87) and cancer-specific survival (HR 0.92) than men ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study has indicated that the tumor deposits to be associated with negative prognostic effect, especially in stage IIIB colon cancer, with a 3.2-fold increased risk of disease recurrence (12). Also, female patients with colorectal cancer showed a slight but significantly better OS than men (13). Similarly, a meta-analysis by Yang et al confirmed this finding when comparing nine studies (14).…”
Section: Discussionmentioning
confidence: 85%